Construction of unital matrix polynomials with mutually distinct characteristic roots - Mel'nyk, O. M.; Мельник, О. М.; Мельник, О. М. (Institute of Mathematics, NAS of Ukraine, 1993)
We investigate the construction of unital matrix polynomials with mutually distinct characteristic roots, namely, their similarity and reducibility by the similarity transformation to block-triangular, block-diagonal, and, in particular, to triangular and diagonal forms. We also study the problem of extracting linear factors.